Utilization of wattpad media to enhance the effectiveness of poetry writing learning for high school students - La Ode Adili; Irianto Ibrahim; Sri Suryana Dinar; La Ode Sahidin; La Ode Syukur; La Aso; La Tike; Saidiman Saidiman; N Nurfadillah; R Risna (Jurnal Konseling dan Pendidikan, 2025)
One of the learning materials for 11th-grade high school students is writing poetry based on short stories. The characteristics of this material direct students to read short stories first to gain inspiration so that they can write poetry well. However, the learning process for this material seems less attractive to students due to the limitations of the learning media used by teachers. One digital medium that can stimulate students' imagination and creativity is the Wattpad application. This study explores the use of Wattpad media to improve the effectiveness of poetry writing learning. The research design used a one-group pretest-posttest design. The research instruments included: (1) student activity observation format, (2) learning outcomes test in the form of pretest and posttest, and (3) student response questionnaire to Wattpad media. There were 24 students who participated in this study. The results showed that student activity reached an average of 4.67 (very effective), and learning outcomes based on N-Gain analysis reached 0.76 (effective). Student responses to Wattpad media reached an average of 4.42 (very effective). This study concludes that the use of Wattpad media can improve the effectiveness of poetry writing learning. The implication is that the use of Wattpad can stimulate creativity and student engagement, leading to better learning outcomes. Indonesian language teachers can utilize Wattpad media for relevant learning materials.